Executive leadership and administrative management in elementary school principals (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2018)
The purpose of the research: To determine the relationship between managerial leadership and administrative management among elementary school principals in the Ricaurte parish of the Mara municipality. The research was descriptive and correlational, using a non-experimental cross-sectional field design. The population consisted of 115 subjects, including administrators and teachers. The results obtained determined that the application of strategic planning by educational managers is low, which leads to deficiencies in management. Guidelines for managerial leadership are proposed with the aim of improving administrative management.